2019
DOI: 10.3390/ijerph16061073
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Road, Railway, and Aircraft Noise on Sleep: Exposure–Response Relationships from Pooled Data of Three Laboratory Studies

Abstract: Objectives: Air, road, and railway traffic, the three major sources of traffic noise, have been reported to differently impact on annoyance. However, these findings may not be transferable to physiological reactions during sleep which are considered to decrease nighttime recovery and might mediate long-term negative health effects. Studies on awakenings from sleep indicate that railway noise, while having the least impact on annoyance, may have the most disturbing properties on sleep compared to aircraft noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…For instance, studies in underwater settings and Intensive Care Units substantially failed to highlight significant alterations of sleep or of the sleep/wake cycle (e.g., Trousselard et al, 2015;Reinke et al, 2019), whereas studies in caves showed an increased SWS (Mogilever et al, 2018), contrarily to what has been reported in polar settings. Instead, the decrease in SWS has been extensively observed during the exposure to a systemic stressor such as noise (Basner and Samel, 2005;Griefahn et al, 2006), or hypoxia (Rojc et al, 2014;Morrison et al, 2017), even if not conclusive. Although few studies exist, psychosocial stressors have also been found to induce similar changes (Kim and Dimsdale, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, studies in underwater settings and Intensive Care Units substantially failed to highlight significant alterations of sleep or of the sleep/wake cycle (e.g., Trousselard et al, 2015;Reinke et al, 2019), whereas studies in caves showed an increased SWS (Mogilever et al, 2018), contrarily to what has been reported in polar settings. Instead, the decrease in SWS has been extensively observed during the exposure to a systemic stressor such as noise (Basner and Samel, 2005;Griefahn et al, 2006), or hypoxia (Rojc et al, 2014;Morrison et al, 2017), even if not conclusive. Although few studies exist, psychosocial stressors have also been found to induce similar changes (Kim and Dimsdale, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Given that it is also present during space-missions, attention must be paid to it. Changes in sleep structure have also been found due to laboratorycontrolled environmental noise both in animals (Rabat et al, 2004) and humans (Basner and Samel, 2005;Griefahn et al, 2006). Basner and Samel (2005), investigated the effects of nocturnal aircraft noise on sleep.…”
Section: Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Noise induced sleep disturbance as demonstrated in experimental human laboratory studies [22][23][24], field trials [25] and observational epidemiological studies [26,27] are thus likely to be on the pathway for detrimental effects on the cardiometabolic system and mental health. Strikingly, evidence for noise effects on various sleep outcomes is only considered "very low" to "moderate" in the recent systematic review of the World Health Organization Environmental Noise Guidelines for the European Region [28].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the average sound pressure level (Leq and similar indicators) may not be the only relevant factor; other noise exposure characteristics not captured in energy-based exposure indicators may also be important. For instance, in experimental sleep studies on noise effects on sleep, different effects have been observed for road, rail, and aircraft noise [22,23]. Thus, the effects of noise on sleep might either be better predicted by the number of noise events [29], the maximum sound pressure level [30], the sound pressure level slope [24,31] or by the order of events [31].…”
Section: Introductionmentioning
confidence: 99%